2011
DOI: 10.1175/2011jcli4113.1
|View full text |Cite
|
Sign up to set email alerts
|

A Climatology of Wintertime Barrier Winds off Southeast Greenland

Abstract: A climatology of barrier winds along the southeastern coast of Greenland is presented based on 20 yr of winter months (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) 22 . Total precipitation rates were larger at DSS than DSN, both typically less than 1 mm h 21 . The total turbulent heat fluxes were shown to have a large range as a result of a large range in 2-m air temperature. Two classes of barrier winds-warm and cold-were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(136 citation statements)
references
References 50 publications
6
130
0
Order By: Relevance
“…Especially the pressure is in excellent agreement with the observations [Harden et al, 2011]. During high wind speed conditions the 10m-winds are underrepresented by ∼1 m s −1 and the 2m-air temperature has a cold bias of ∼2°C.…”
Section: Datasupporting
confidence: 86%
See 4 more Smart Citations
“…Especially the pressure is in excellent agreement with the observations [Harden et al, 2011]. During high wind speed conditions the 10m-winds are underrepresented by ∼1 m s −1 and the 2m-air temperature has a cold bias of ∼2°C.…”
Section: Datasupporting
confidence: 86%
“…Greenland itself likely plays a crucial role in forcing the cross-coastal flows, as previous studies have found that the interaction of the large-scale atmosphere with the high topography (shown in Figure 1-1a) creates strong wind events, particularly near the east coast [Moore, 2003]. These include tip jets around the southern tip of Greenland [Doyle and Shapiro, 1999, Våge et al, 2009, Moore and Renfrew, 2005, Renfrew et al, 2009a, Outten et al, 2009 and barrier winds at different locations along the east coast [Moore and Renfrew, 2005, Harden et al, 2011, Harden and Renfrew, 2012, Moore, 2012, and it was found that both types of wind events are associated with deep cyclones. In fact, the regions off the southwest, southeast and east Greenland coast are characterized by a particularly high cyclone frequency and large deepening rates [Zhang et al, 2004, Tsukernik et al, 2007.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations